2013
DOI: 10.1007/s12079-013-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 induces EMT reprogramming of porcine bladder urothelial cells into collagen producing fibroblasts‐like cells in a Smad2/Smad3‐dependent manner

Abstract: Activation of fibroblasts and their differentiation into myofibroblasts, excessive collagen production and fibrosis occurs in a number of bladder diseases. Similarly, conversion of epithelial cells into mesenchymal cells (EMT) has been shown to increase fibroblasts like cells. TGF-β1 can induce the EMT and the role of TGF-β1-induced EMT during bladder injury leading to fibrosis and possible organ failure is gaining increasing interest. Here we show that EMT and fibrosis in porcine bladder urothelial (UC) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 65 publications
(70 reference statements)
3
47
0
Order By: Relevance
“…Islam et al 22 found that TGF-β1 induces the development of bladder fibrosis via a Smad2/Smad3-dependent MMP2/MMP9 signal pathway. Thus, like IL-6, TGF-β1 is a multifunctional cytokine that has different roles in different pathways in the development of fibrotic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al 22 found that TGF-β1 induces the development of bladder fibrosis via a Smad2/Smad3-dependent MMP2/MMP9 signal pathway. Thus, like IL-6, TGF-β1 is a multifunctional cytokine that has different roles in different pathways in the development of fibrotic responses.…”
Section: Discussionmentioning
confidence: 99%
“…SB431542 (Selleck Chemicals, USA), which is a potent and selective inhibitor of the TGF-β receptor I (TβR I), was demonstrated to suppress TGF-β1-induced extracellular matrix in different types of cells (Islam et al 2014;Laping et al 2002;Zhao et al 2006). Polyclonal antibodies against alpha-smooth muscle actin (α-SMA), pro-collagen type I alpha 1 (pro-COL1A1), TβR I, TGF-β receptor II (TβR II), pSmad2/3, Smad4, and ERK were obtained from Santa Cruz Biotechnology, USA.…”
Section: Reagentsmentioning
confidence: 99%
“…Receptor-associated SMADs interact with EMT-TFs such as AP-1 and Snail [36].TGF-β1 treatment induces a significant change of cellular morphology depicted by increasing α-SMA and N-cadherin and corresponding decreased E-cadherin via a SMAD2/SMAD3-dependent manner. Notably, α-SMA and N-cadherin increases are dependent on both SMAD2 and SMAD3, whereas Ecadherin is down-regulated by TGF-β1 only in a SMAD3-dependent manner [37]. Some studies have confirmed that E-cadherin also could be suppressed by TGF-β through ZEB, Snail and HMGA2.…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 99%